PENGARUH MEMINUM TABLET EFFERVESCENT TERHADAP pH SALIVA PADA MAHASISWA POLTEKKES KEMENKES YOGYAKARTA - Lisa Endreswari; Sri Ediati; Siti Hidayati (Poltekkes Kemenkes Yogyakarta, 2014)
Background: The occurrence of dental caries (tooth decay), which affects many people of Indonesia begins with the process due to demineralization of emailby acid that comes from food and beverages, which one is the effervescent tablet. Based on a research, it proved that the effervescent tablet cause corrosion to the teeth. This is happen because of pH of the effervescent tablet solution makes the mouth condition become acic. The goal of this study is to determine the effect of drinking effervescent tablet to the pH of saliva. Method: The research was pre-experimental with pretest and posttest design. The study was conducted in six departments in the Poltekkes Kemenkes Yogyakarta on April 23rd until May 5th 2012. The population consist of 35 people, 29 peopledrawn from the population as the samples using simple random sampling technique. Research variables are the pH of saliva and effervescent tablets. Analysis of the data used is the Chi square test with significance level = 0.05. Result: The Chi square test earned an average pH of saliva before drinkingthe effervescent tablet which contain calcium of 7.3, and the average pH of saliva after drinking effervescent tablet which contain calcium of 7.5. The average pH of saliva before drinking the effervescent tablet which contain thyme of 7.4, and the average pH of saliva after drinking effervescent tablet which contain thyme of 7.7. The result of chi square test showed there was no significant effect is equal to 0.800 and 0.664 with a significance level of 0.05. Conclusion: It proved that was no effect of drinking effervescent tablets to the salivary pH in Poltekkes Kemenkes Yogyakarta students.